2009
DOI: 10.1038/nbt.1539
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific silencing of mutant huntingtin and ataxin-3 genes by targeting expanded CAG repeats in mRNAs

Abstract: Many neurological disorders are caused by expanded trinucleotide repeats1, including Machado-Joseph Disease (MJD)2 and Huntington Disease (HD)3. MJD and HD are caused by expanded CAG repeats within the ataxin-3 (ATXN3) and huntingtin (HTT) genes. Inhibiting expression of ATXN3 or HTT are promising therapeutic strategies, but indiscriminant inhibition of wild-type and mutant alleles may lead to toxicity. We hypothesized that expanded triplet repeat mRNA might be preferentially recognized by complementary oligom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
267
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(277 citation statements)
references
References 34 publications
10
267
0
Order By: Relevance
“…2′-OMe ASOs have also been shown to selectively target expanded CUG repeats in DM1 myoblasts (13). Another study showed that ASOs used to inhibit translation of CAG expansions in Huntington disease only affected the expanded huntingtin allele but not the wild-type allele (26). This provides evidence that the ability to preferentially target expanded repeat sequence may be common to other ASO therapies.…”
Section: Discussionmentioning
confidence: 76%
“…2′-OMe ASOs have also been shown to selectively target expanded CUG repeats in DM1 myoblasts (13). Another study showed that ASOs used to inhibit translation of CAG expansions in Huntington disease only affected the expanded huntingtin allele but not the wild-type allele (26). This provides evidence that the ability to preferentially target expanded repeat sequence may be common to other ASO therapies.…”
Section: Discussionmentioning
confidence: 76%
“…6,11,21 However, only a few studies have assessed silencing in patient-derived cells, which exhibit physiologically relevant levels of endogenous expression. 3,[22][23][24][25] We sought to address whether polyQ patient-derived fibroblasts might be a useful model for assessing therapeutic strategies, such as comparing allele-specific and non-allele-specific silencing approaches in genetically accurate cells. All the polyQ patient-derived cell line studies to date 3,[22][23][24][25][26] have focused on the development of allelespecific silencing approaches targeting SNPs linked to the mutation and/or the mutation itself, and show increasingly promising results.…”
Section: Discussionmentioning
confidence: 99%
“…5). Given this, the development of nucleic acid therapy by noncoding small RNAs could be an ideal approach to selectively silence mutant htt [115,116]. Harper et al [117] showed that RNA interference using adeno-associated virus-small hairpin RNA (shRNA) improves motor deficits and neuropathological phenotypes in a transgenic (N171-82Q) mouse model of HD.…”
Section: Rna Interference and Noncoding Small Rnasmentioning
confidence: 99%